Wheat Variety-Specific Grain Yield Response to Plant Density Under Intensive Management Conditions in Western Kansas - R. P. Lollato; K. Mark; B. R. Jaenisch (Kansas Agricultural Experiment Station Research Reports, 2020)
Seeding rate determines the first yield component of field crops, which is the plant population. However, wheat is less responsive to plant populations than other crops due to the high plasticity in tillering potential, and this responsiveness depends on resource availability. The objective of this project was to evaluate winter wheat population, grain yield, and grain test weight responses to seeding rate and its interaction with variety in a highly managed production system where manageable stresses were limited. Experiments evaluating the response of the wheat varieties ‘Joe,’ ‘WB-Grainfield,’ ‘Langin,’ and ‘LCS Revere’ to seeding rates ranging from 200,000–1,000,000 seeds per acre were established in a field managed by growers who consistently win state and national wheat yield contests near Leoti, KS. Trials were established at a relatively late date in 2017–2018 (delayed by pre-sowing rainfall), and at the optimal timing during 2018–2019. Growing seasons contrasted in that 2017–2018 was dry (approximately 6 inches in-season precipitation) and had warm grain filling conditions, and 2018–2019 was cool and moist (appx. 13 inches in-season precipitation). Stand count increased with increases in seeding rate both years but final population was closer to the target population during 2017–2018. Grain yield response to seeding rate and to variety depended on year, but all varieties responded similarly to seeding rate. In 2017–2018, grain yield increased linearly from appx. 40–60 bushels per acre with increases in seeding rate from 200,000–400,000 seeds per acre. During 2018–2019, the lowest yield was recorded across varieties in the plots with 200,000 seeds per acre, with the treatments ranging from 400,000–1,000,000 seeds per acre all resulting in the same yield level. Grain yield as affected by emerged plant population (instead of seeding rate) showed similar trends, though quadratic relationships indicated a maximum yield at about 500,000–580,000 plants per acre in 2018–2019. Grain test weight was impacted by the interaction of variety, seeding rate, and year. Greatest test weight values resulted in 2017–2018, when the test weight of all varieties responded in a quadratic way to seeding rates. In 2018–2019, there was no clear trend in varieties’ test weight responses to population. These results suggest that wheat grain yield responses to seeding rate (and to plant population) are more dependent on sowing date and weather conditions than on variety, with optimum sowing times and a warm fall allowing for seeding rate as low as 400,000 seeds per acre without yield penalty. Meanwhile, later sowing dates and cooler fall conditions required seeding rates of up to 1,000,000 seeds per acre to maximize grain yield.
Keywords: wheat; seeding rate; population; yield potential